2022
DOI: 10.3390/life12060903
|View full text |Cite
|
Sign up to set email alerts
|

Bone Tissue Engineering through 3D Bioprinting of Bioceramic Scaffolds: A Review and Update

Abstract: Trauma and bone loss from infections, tumors, and congenital diseases make bone repair and regeneration the greatest challenges in orthopedic, craniofacial, and plastic surgeries. The shortage of donors, intrinsic limitations, and complications in transplantation have led to more focus and interest in regenerative medicine. Structures that closely mimic bone tissue can be produced by this unique technology. The steady development of three-dimensional (3D)-printed bone tissue engineering scaffold therapy has pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 142 publications
0
26
0
Order By: Relevance
“…This phenomenon is explained by weak non-covalent immobilization between TSA molecules and the polymeric chain of CS. Evidence has shown that microfabrication techniques, such as 3-dimensional printing or electrospinning and using a microsphere release system, can enable drug molecules to sustain release in sequential manners [ 40 , 41 , 42 ]. Further studies should be conducted to modify the fabrication procedure and TSA loading method, resulting in a controlled release fashion.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is explained by weak non-covalent immobilization between TSA molecules and the polymeric chain of CS. Evidence has shown that microfabrication techniques, such as 3-dimensional printing or electrospinning and using a microsphere release system, can enable drug molecules to sustain release in sequential manners [ 40 , 41 , 42 ]. Further studies should be conducted to modify the fabrication procedure and TSA loading method, resulting in a controlled release fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Bone grafts are used in medical practice to the benefit of millions of American patients in need for restorations required as a result of congenital defects, trauma, cancer, or other forms of skeletal damage. These grafts are made either from natural bone, or increasingly from biocompatible materials, as we gain a better understanding of the body's response to their properties, to the incorporated extracellular matrix components, and to the use of cellular constituents (32).…”
Section: Discussionmentioning
confidence: 99%
“… 54–56 However, conventional 3D-printed bioceramics scaffolds also exhibit disadvantages such as single function, difficulty inducing angiogenesis, low bone formation efficiency, inability to treat tumors, and ease of bacterial reproduction, which hinder the development of bioceramics scaffolds. 57 Due to the advancement of research, bioceramic scaffolds composed of a single material are rarely employed. Based on traditional calcium phosphate-based and calcium silicon-based materials, 3D-printed bioceramics scaffolds are further optimized by methods such as apparent function change, trace element doping, and nanostructure construction, making them an ideal alternative material in bone tissue engineering.…”
Section: Application Of Different Types Of 3d Printed Biological Scaf...mentioning
confidence: 99%